EVALUASI KINERJA DISEMINASI TEKNOLOGI INTEGRASI TERNAK KAMBING DAN KOPI DI BONGANCINA, BALI - SUDANA, WAYAN (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 5, No. 3 November 2005, 2012)
According to AIAT vision and mission, AIAT should be able to develop local specific alternative package of agriculture technology. This study has been conducted to evaluate the performance of dissemination which has been done by AIAT, especially for the integration technology livestock (goat) with coffee crop. This evaluation were conducted by interviewing stakeholder and beneficiaries start from provincial level, district, sub district level, and the end at farmer group. Result of evaluation showed performance of dissemination activities has been done properly by AIAT, especially at provincial and district level. But at farmer group especially at target group or target area outside of farmer cooperator not yet was done maximally. Dissemination should be emphasized for the target group or target areas immediately after package of technology described, through some ways of dissemination methods. Based on SWOT analysis, there are strong opportunity to develop farmer coffee plantation, because productivity and efficiency of farmer coffee are still low.
Keywords: Goat, Coffee Plantation, Dissemination and Technology